2022
DOI: 10.3390/nano12224066
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Storage Filled with Peat-Derived Carbon Adsorbent: Influence of Nonisothermal Effects and Ethane Impurities on the Storage Cycle

Abstract: Adsorbed natural gas (ANG) is a promising solution for improving the safety and storage capacity of low-pressure gas storage systems. The structural–energetic and adsorption properties of active carbon ACPK, synthesized from cheap peat raw materials, are presented. Calculations of the methane–ethane mixture adsorption on ACPK were performed using the experimental adsorption isotherms of pure components. It is shown that the accumulation of ethane can significantly increase the energy capacity of the ANG storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It can therefore be concluded that under high pressure, the S BET is still the main factor determining the adsorption amount. (2) The potential well between methane molecules and the AC is larger than that in the 3D-GS. Considering the heterogeneous surface of carbon-based materials, the framework to determine the potential well between adsorbate-adsorbent is built by PSD determined by 2D-NLDFT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It can therefore be concluded that under high pressure, the S BET is still the main factor determining the adsorption amount. (2) The potential well between methane molecules and the AC is larger than that in the 3D-GS. Considering the heterogeneous surface of carbon-based materials, the framework to determine the potential well between adsorbate-adsorbent is built by PSD determined by 2D-NLDFT.…”
Section: Discussionmentioning
confidence: 97%
“…Methane is one of the most important energy sources in natural gas and biogas [1], but the low volumetric and gravimetric storage capacities of methane at room temperature still restrict its application as fuel in mobile vehicles [2,3]. It is still a challenge to safely and effectively improve the capacity of methane storage [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since OPLSAA provides the opportunity to consider all of the components of the adsorbate–adsorbent and adsorbate–adsorbate interactions as much as possible, it is widely and effectively used to describe various adsorption systems. …”
Section: Methodsmentioning
confidence: 99%
“…Since the total energy of interactions in the adsorption system includes contributions from all of the molecules in the model pore, this result can be attributed to a predominant contribution of the methane−methane interactions in the 95% CH 4 /5% C 2 H 6 mixture compared to the ethane−ethane and ethane−pore wall interactions. As a result, the methane molecular associates are formed near the pore walls, 60 and they push a few ethane molecules into the central part of the pore.…”
Section: Thermodynamic Properties Of Adsorption Systemsmentioning
confidence: 99%
“…Two research works in this Special Issue studied the adsorption and storage of natural gases on defined nanomaterials. [ 7 , 8 ] First, Shkolin et al [ 7 ] synthesized an active carbon nanomaterial from cheap peat raw materials and investigated its structural–energetic and adsorption properties towards natural gas (ANG). The study provides insights into the solution for improving the safety and storage capacity of low-pressure gas storage systems.…”
mentioning
confidence: 99%